(3WHbGJ GdTGaYjI GdcHQis - (3YHO GdhgGH Hf Ydj Hf YHO GdcGaj GdSHcj, CHh fUQ , JGL GdOjf , J (B771 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3ef GdWHbI GdQGHYI ajef Jhai Hjf GdCQHY eFI hGdNeS eFI JQLeI (B: (3eMeO Hf CMeO Hf YHO GdHGbi eGJ ai eSJgd UaQ s
(3BNQgG (B:s
(3BNQ GdehLhO efg JQLeI Ydi Hf eMeO Hf MehjI hHYOgG PcQ KdGK aJGhi ef aJGhi GHf GdHRQi hZQGFHI hVQH GdQLd RhLJg Ydi JQc GdUdGI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B184 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B225s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B108 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B105 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 - (3U (B144 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJGQjNs